Quality of work life impact to workers’ performance at Padiberas Nasional Berhad (BERNAS) - Nurul Syifaa’, Ramli (2015)
The goal of this research is to study between quality of work life and employees performance. For the quality of work life is a set as the independent variable. Then, the employees’ performance of the work is the dependent variable. One hundred and forty respondents from the Unit of Local Rice of Padiberas Nasional Berhad (BERNAS) around Kedah, were surveyed by questionnaires. The collected data were analyzed by using Cronbach’s Alpha (reliability analysis), correlation analysis, regression analysis and descriptive statistics. The objectives of the research are to identify the quality of work life factors’ in the organization and the second one is to analyze the relationship between quality of work life and workers’ performance. Results shows that there is significant positive relationship between quality of work life and employees’ performance and the finding are in accordance with previous researchers.